Development and characterization of biomass based novel adsorbent in the removal of Congo red dye by adsorption - Dawood, Sara A. (Curtin University, 2013)
Pine cone (Pinus. radiate) biomass is a low cost agricultural solid waste. Raw pine cone, acid treated pine cone and synthesized pine cone based activated carbon have been successfully used here as effective, environmentally friendly and low cost adsorbents in the removal of anionic dye Congo red from aqueous solution by adsorption.